Translation Strategy Through Pragmatic Lens: Speech Act Analysis on The Campaign Media - Risma Julistiana; Wida Mulyanti; Setyo Wati (Universitas Subang, 2024)
Communication plays an essential role in transporting messages, feelings, ideas, or even an influence. They are transmitted both verbally and non-verbally. This study elaborates on the use of speech acts in campaign advertising, specifically on billboards and posters as a means of conveying a candidate’s message through written communication in non-English languages in Tasikmalaya City. The capacity to use language in an assortment of settings while reflecting the relationship between the speakers and social cultural context of the situation is known as pragmatic competence. This research is a descriptive qualitative study; data analysis was conducted in two steps. firstly, it was carried out through a translation process which was done by English Education Department students in varied study grades; furthermore, the translation result was analyzed by the researcher to seek Chesterman's translation strategy through the lens of Pragmatics. The writer applied Miles and Huberman's data reduction, data display, and conclusion drawing to analyse the data. The data reduction categorized the message into several categories of illocutionary acts using the translations that have been organized, then it was continued by classifying them according to Searle’s theory of speech act. This study shows that coherence change at 42.3%, trans editing at 23.1%, explicit change at 19.2%, cultural filtering at 11.5%, and illocutionary change at 3.8%; those reflect the translation strategy usage. Furthermore, the illocutionary act shows assertive 58.3%, directive 25%, and commissive 16.7%. Moreover, the pedagogical implications of the analysis are leading students to the awareness that translation can be done using various strategies, enhancing students’ understanding of translation strategies, and sharpening students’ critical thinking.